55.9k views
4 votes
If f(x)= -4x + 3 and g(x) = 3x² + 2x - 4 find (f+g)(x)

If f(x)= -4x + 3 and g(x) = 3x² + 2x - 4 find (f+g)(x)-example-1

1 Answer

6 votes

Answer:

A

Explanation:

We have the two functions:


f(x)=-4x+3\text{ and } g(x)=3x^2+2x-4

And we want to find (f+g)(x).

Note that this is the same thing to f(x)+g(x). Therefore:


\begin{aligned} (f+g)(x)&=f(x)+g(x) \\ &=(-4x+3)+(3x^2+2x-4) \end{aligned}

We simply substituted them for their equations.

Simplify. Combine like terms:


=(3x^2)+(-4x+2x)+(3-4)

Add:


=3x^2-2x-1

Hence, our answer is A.